Impact of ABO blood type on the risk of atrial fibrillation recurrence after catheter ablation - Amioka, Michitaka; Kinoshita, Hiroki; Sairaku, Akinori; Shokawa, Tomoki; Nakano, Yukiko (American Heart Journal Plus: Cardiology Research and Practice, 2024)
Blood types are classified based on the specific antigenic characteristics they possess. Despite documented associations between antigens and inflammation, a scarcity of data exists concerning the impact of antigens on atrial fibrillation (AF). OSHOH-rhythm study is a multi-center, prospective observational study of 601 patients who underwent catheter ablation for AF. We examined the correlation between blood type groups and both the incidence and recurrence of AF. Additionally, we analyzed the recurrence of AF across antigenic profiles. The frequencies of individual blood types were 239 (39.8 %), 190 (31.6 %), 122 (20.3 %), and 50 (8.3 %) for A, O, B, and AB, respectively, aligning closely with the prevalent blood type distribution among the Japanese populace. During follow-up period (18.8 months, median), AF recurrence occurred in 96 patients (22.4 %) lacking the B antigen (A and O), and 26 patients (15.1 %) possessing B antigen (B and AB), respectively (Log-rank test: P = 0.034). A multivariate analysis demonstrated that blood types lacking the B antigen (hazard ratio [HR], 1.55; 95 % CI, 1.01 to 2.42; P = 0.037), hypertension (HR, 1.51; 95 % CI, 1.05 to 2.17; P = 0.026) and non-paroxysmal AF (HR, 1.70; 95 % CI, 1.17 to 2.47; P = 0.005) were independently associated with the recurrence of AF. This study elucidates that, despite the absence of direct correlation between blood types and the occurrence of AF, blood types devoid of the B antigen exhibit an enhanced predisposition to AF recurrence. Nonetheless, the intricate mechanism linking blood type to recurrence remains elusive, warranting further comprehensive foundational research on blood types. •The distribution of atrial fibrillation patients according to blood type was in concordance with the proportions of blood types observed within the Japanese populace.•Notably, there was no clear difference in incidence of atrial fibrillation between the different blood types.•Non-B antigen blood types (A and O) emerged as independent risk factors for the recurrence of atrial fibrillation after catheter ablation.•This study constituted a research endeavor that elucidated variations in the recurrence rates of atrial fibrillation across different blood groups, thereby implying a novel clinical approach.